Workplace bullying and its association with depression and self-esteem amongst health care workers in selected hospitals in Sarawak - Chang Chung Meng,, Peter; Su, Anselm-Ting; Mohd Mizanur, Rahman (Malaysian Medical Association, 2017)
ABSTRACT Introduction: Bullying at the workplace has been recognised as an increasing problem amongst healthcare staff, and also associated with a low self-esteem and depression. This study was aimed to determine the proportion of bullying amongst healthcare workers in selected hospitals in Sarawak and its association between depression and self-esteem. Methods: A cross sectional study using selfadministered questionnaires was done in three selected hospitals in Sarawak. The questionnaires were distributed to doctors, nurses and medical assistants during their teaching sessions. The questionnaires consisted of socio-demographics, Negative Acts Questionnaire, Beck Depression Inventory, and Rosenberg Self-Esteem scale. A total of 426 samples were included for analysis, after discarding 72 samples due to grossly missing information. The response rate was 71.1%. Results: Majority of the respondents were of the age group 25 to 29 years old. Nurses comprised 45.5% of the study population, followed by doctors (37.8%), whilst the rest were medical assistants and midwives. Based on the definition of bullying as at least two occurrences of any negative act either on a weekly or daily basis,20.7% of respondents had been bullied. 22.5% of the study group had mild to severe depression, and 8.5% had a low self-esteem. There was an association between depression and being bullied, with a p value of <0.001. Those healthcare workers who had a low self-esteem were associated with higher exposure to bullying, with a p value <0.001. The factors associated with bullying werethe younger age group, shorter length of service, shifting work, non-managerial position and the designation as a doctor. Discussion: A significant proportion of healthcare workers had been bullied, and bullying exposure was shown to be associated with depression and low selfesteem. Hence, regular screening for bullying, depression and low self-esteem should be done to enable early intervention.